Microbial Stimulation by Mycoplasma fermentans Synergistically Amplifies IL-6 Release by Human Lung Fibroblasts in Response to Residual Oil Fly Ash (ROFA) and Nickel - Gao, Fei (Toxicol Sci, 2004)
Mycoplasma (MP), such as the species M. fermentans, possess remarkable immunoregulatory properties and can potentially establish chronic latent infections with little signs of disease. Atmospheric particulate matter (PM) is a complex and diverse component of air pollution associated with adverse health effects. We hypothesized that MP modulate the cellular responses induced by chemical stresses such as residual oil fly ash (ROFA), a type of PM rich in transition metals. We assessed the release of interleukin-6 (IL-6), a prototypic immune-modulating cytokine, in response to PM from different sources in human lung fibroblasts (HLF) deliberately infected with M. fermentans. We found that M. fermentans and ROFA together synergistically stimulated production of IL-6 compared to either stimuli alone. Compared to several other PM, ROFA appeared most able to potentiate IL-6 release. The potentiating effect of live MP infection could be mimicked by M. fermentans-derived macrophage-activating lipopeptide-2 (MALP-2), a known Toll-like receptor-2 agonist. The aqueous fraction of ROFA also contained potent IL-6 inducing activity in concert with MALP-2, and exposure to several defined metal salts indicated that Ni and, to a lesser extent V, (but not Cu) could synergistically act with MALP-2 to induce IL-6. These data indicate that microorganisms like MP can interact with environmental stimuli such as PM-derived metals to synergistically activate signaling pathways that control lung cell cytokine production and, thus, can potentially modulate adverse health effects of PM exposure.